2021
DOI: 10.1098/rsbl.2021.0167
|View full text |Cite
|
Sign up to set email alerts
|

Brief exposure to warm temperatures reduces intron retention in Kdm6b in a species with temperature-dependent sex determination

Abstract: Animals with temperature-dependent sex determination (TSD) respond to thermal cues during early embryonic development to trigger gonadal differentiation. TSD has primarily been studied using constant temperature incubations, where embryos are exposed to constant male- or female-producing temperatures, and these studies have identified genes that display sex-specific expression in response to incubation temperature. Kdm6b , a histone demethylase gene, has received specific attention as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Histone modifiers jarid2 (Jumonji And AT-Rich Interaction Domain Containing 2) and kdm6b (Lysine Demethylase 6B) play a role in high temperature induced sex reversal in P. vitticeps [ 19 , 38 ] and in other evolutionary disparate TSD species [ 16 , 17 , 20 , 39 41 ]. Epigenetic regulation is also implicated in GSD sytems, for example in mice, where a Jumonji family member, Jmjd1a (Lysine Demethylase 3A), directly regulates expression of the sex determining gene Sry [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Histone modifiers jarid2 (Jumonji And AT-Rich Interaction Domain Containing 2) and kdm6b (Lysine Demethylase 6B) play a role in high temperature induced sex reversal in P. vitticeps [ 19 , 38 ] and in other evolutionary disparate TSD species [ 16 , 17 , 20 , 39 41 ]. Epigenetic regulation is also implicated in GSD sytems, for example in mice, where a Jumonji family member, Jmjd1a (Lysine Demethylase 3A), directly regulates expression of the sex determining gene Sry [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The findings from this research open up many new avenues for future research, including determining the range of temperatures at which the ΔN variants may be functioning in P. vitticeps and demonstrating their function in regulating sex determination cascades. The effect temperature fluctuations during incubation in natural nests on splicing modulation also needed to be investigated ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Temperature-dependent alternative splicing is commonly observed in TSD reptiles and has been suggested to be an essential process in both TSD (24)(25)(26)(27)(28)(29) and sex reversal (30,31). For example, genes kdm6b and jarid2 and their differential splicing patterns have been implicated in the regulation of TSD in two species, the American alligator (Alligator mississippiensis) and the redeared slider turtle (Trachemys scripta) (32)(33)(34)(35)(36). Functional work in T. scripta has shown that KDM6B demethylates the promotor of a key sex gene dmrt1 (33) to determine the trajectory of the sex differentiation pathway (34,37).…”
Section: Introductionmentioning
confidence: 99%
“…Studies carried out by Ge et al (2018) at constant temperatures showed that during TSP, the expression of kdm6b increases and that its repression leads to the development of female gonads, significantly increasing the expression of aromatase and foxl2 genes. In T. scripta, alternative splicing of kdm6b occurs due to temperature (Deveson et al, 2017) and has an important role in sex determination by temperature (Ge et al, 2018;Marroquín-Flores et al, 2021). At male-producing incubation temperatures, there is an increase in transcripts of kdm6b without introns.…”
Section: Epigenetics On Tsdmentioning
confidence: 99%
“…At male‐producing incubation temperatures, there is an increase in transcripts of kdm6b without introns. However, when the eggs are incubated at fluctuating temperatures and the temperature increases, there is an increase in the amount of transcripts without introns, producing changes in the total expression of the protein (Marroquín‐Flores et al, 2021). The intron transcript would be responsible for increasing transcription rate of kdm6b , positively regulating drmt1 and generating male production in T. scripta .…”
Section: Introductionmentioning
confidence: 99%